Hubungan Dukungan Keluarga dan Efikasi Diri dengan Kualitas Hidup Lansia Penderita Diabetes Melitus - Trisna Vitaliati; Nurul Maurida; Irwina Angelia Silvanasari (Jurnal Ilmiah Keperawatan STIKES Hang Tuah Surabaya, 2023)
People with Diabetes Mellitus need long-term care and treatment to improve their quality of life. Family support and self-efficacy are believed to have an influence on the quality of life of elderly people with diabetes mellitus. The objective of the study was to identify family support, self-efficacy and quality of life for elderly people with diabetes mellitus. This study is a descriptive analytic study with a cross-sectional approach.  The sample in this study were elderly people with diabetes mellitus who were selected using a purposive sampling technique with a total of 54 respondents. Furthermore, univariate data analysis was carried out using the frequency distribution and statistical tests using the Spearman Rho Test. The results of the Rho Spearman analysis showed that family support was positively correlated with the quality of life of elderly people with diabetes mellitus (rho=0.579; p<0.01). Meanwhile, the results of the Rho Spearman analysis showed that self-efficacy correlated positively with the quality of life of elderly people with diabetes mellitus (rho=0.537; p<0.01). The recommendation from the results of this study, is that nurses can increase family support and self-efficacy for elderly people with diabetes mellitus by forming a support group consisting of families who have elderly family members with diabetes mellitus so that they can share information related to how to provide family support to provide positive reinforcement and motivation to elderly people with hypertension so that their quality of life increases.